Analysis of Nasofrontal and Nasal Tip Angles between Bengali and Manipuri Adult Males of Bangladesh: A Photo-Anthropometric Study - Pathan, Md Azmal Khan; Paul, Pankaj; Akhter, Najnin; Choudhury, Sudipta; Najmin, Marufa; Hasan, Abul; Chowdhury, Ferdaucy (Journal of Brahmanbaria Medical College, 2026)
Background: Photo anthropometry is a scientific method that involves using photographs to analyze the proportions of various body parts and to obtain measurements, which can vary significantly across different racial groups. This study aimed to explore photo-anthropometric variations by evaluating the nasofrontal and nasal tip angles of the external nose in Bengali and Manipuri adult males residing in Bangladesh. Materials and methods: This cross-sectional analytical study was carried out in the Department of Anatomy at Sylhet MAG Osmani Medical College, Sylhet, between January 2022 and December 2022. Fifty (50) Bengali and fifty (50) Manipuri adult males, aged 25 to 59 years, were chosen through convenient sampling. Photoanthropometric methods were used to collect data from the Sylhet region. The results were presented as mean ± standard deviation, and the two-sample mean "Z" test was employed to compare findings between the groups. Results: The angular measurements of the external nose, the nasofrontal and nasal tip angles, were significantly higher in Manipuri adult males compared to Bengali adult males (p£0.05). Conclusion: The findings of this study will be valuable in the fields of Anatomy, Plastic Surgery, Forensic Medicine, Genetics, and Anthropology for purposes such as identification, planning corrective surgical procedures, and designing nasal models for different ethnic groups. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 3-7